Prevalensi dan Karakteristik Pasien Tuberkulosis Paru Resisten Obat (TB-RO) dengan Diabetes Melitus Tipe 2 di Klinik TB-RO Rumah Sakit Umum Pusat Dr. Hasan Sadikin, Bandung - Maulida, Diva Harnum; Dewi, Intan Mauli Warma; Santoso, Prayudi; Cahyadi, Adi Imam; Kusumawati, Maya; Kulsum, Iceu Dimas (UI Scholars Hub, 2024)
Introduction. Diabetes mellitus (DM) patients have a higher risk of tuberculosis (TB) infection, including the risk of drug- resistant (DR)-TB infection, compared to those without DM. Data on the characteristics of pulmonary DR-TB with DM in Indonesia are still very limited. The management of pulmonary DR-TB with DM should consider multiple factors, such as drug interactions between DM medication and anti-TB drugs, as well as potential exacerbation of DM complications by anti-TB drugs side effects. Effective management of pulmonary DR-TB patients with DM will improve treatment outcomes. This study aimed to determine the prevalence and characteristics of pulmonary DR-TB patients with type 2 DM at the DR-TB clinic of Dr. Hasan Sadikin Central General Hospital, Bandung. Methods. This cross-sectional study was conducted at the Drug Resistant Tuberculosis (DR-TB) Clinic of Dr. Hasan Sadikin Central General Hospital, Bandung, during the period of January 2020 to May 2023. Data were obtained from the medical records of patients with drug resistant pulmonary tuberculosis and type 2 DM. The study included patients diagnosed with drug resistant pulmonary tuberculosis and type 2 DM who were aged 18 years or older. Data analysis was performed using descriptive statistical methods, and normality test was conducted using the Kolmogorov-Smirnov test. Results. The prevalence of pulmonary DR-TB cases with Type 2 DM was 11.17%. Out of a total of 82 samples, more than half had normal BMI (61.04%), diagnosed with MDR-TB (74.39%). The duration of Type 2 DM were in average between 1-5 years (53.16%), with an HbA1c value ≥7% in 94.20% of the patients. Infiltrates were found in 46.27% of radiological findings. Anemia was present in 54,88% of participants, with an average and standar deviation hemoglobin level of 12.15 (± 1.75) g/dL. Conclusions. The prevalence of pulmonary drug-resistant tuberculosis with type 2 DM at Dr. Hasan Sadikin Central General Hospital, Bandung, is 11,17%. The majority of patients had uncontrolled type 2 DM (HbA1c ≥7%), normal BMI, positive sputum mycobacteriology, and the primary chest X-ray finding is infiltrate. Future studies are necessary to determine the clinical and treatment outcome of these patients.